STABILITY AND DYNAMICS OF THE CONTINENTAL TECTOSPHERE - Shapiro S.S.; Hager B.H.; Jordan T.H. (My University, 1999)
Continental cratons overlie thick, high-viscosity, thermal and chemical boundary layers, where the chemical boundary layers are less dense than they would be due to thermal effects alone, perhaps because they are depleted in basaltic constituents. If the continental tectosphere is the same age as the overlying Archaean crust, then the continental tectosphere must be able to survive for several billion years without undergoing a convective instability, despite being both cold and thick. Since platforms and shields correlate only weakly with Earth's gravity and geoid anomalies, acceptable models of the continental tectosphere must also satisfy this gravity constraint. We investigate the long-term stability of the continental tectosphere by carrying out a number of numerical convection experiments within a two-dimensional Cartesian domain. We initiate our experiments with a tectosphere (thermal and chemical boundary layers) immersed in a region of uniform composition, temperature, and viscosity, and consider the effects on the stability of the tectosphere of (1) activation energy (used to define the temperature dependence of viscosity), (2) compositional buoyancy, and (3) linear or non-linear rheology. The large lateral thermal gradients required to match oceanic and tectosphere structures initiate the dominant instability, a "drip" which develops at the side of the tectosphere and moves to beneath its center. High activation energies and high background viscosities restrict the amount and rate of entrainment. Compositional buoyancy does not significantly change the flow pattern. Rather, compositional buoyancy slows the destruction process somewhat and reduces the stress within the tectosphere. With a non-Newtonian rheology, this reduction in stress helps to stiffen the tectosphere. In these experiments, dynamical systems that adequately model the present ocean-continent structures have activation energy E* ≥ 180 kj mole -1-a value about one third the estimate of activation energy for olivine, E* ≈ 520 kJ mole-1. Although for E * ≈ 520 kJ mole-1, compositional buoyancy is not required for the tectosphere to survive, the joint application of longevity and gravity constraints allows us to reject all models not containing compositional buoyancy, and to predict that the ratio of compositional to thermal buoyancy within the continental tectosphere is approximately unity. © 1999 Published by Elsevier Science B.V. All rights reserved.
Keywords: CONDUCTIVE COOLING; CONTINENTAL TECTOSPHERE; DYNAMICS; MANTLE CONVECTION; MANTLE RHEOLOGY